P244 Paediatric liaison psychiatry – are students aware of the overlap with mental and physical health?. (June 2019) - Richardson, SC; Oketah, ON; Negm, H; Barrett, E
Abstract : Aim: To assess medical students' knowledge and expectations pre and post a structured teaching session regarding mental health needs of young people in hospital. The objective is to analyse the effectiveness of the teaching session and to modify the teaching pack accordingly. Methods: Fifth year medical students were given a survey to complete at the start of a 3 hour teaching session on mental health needs of children in hospital. Students were asked basic knowledge questions and their learning objectives. The students were surveyed again at the end of the teaching to review if the learning outcomes were met and if basic knowledge had improved. Results: 87% (34/39) of the pre-teaching questionnaires and 77% (30/39) post teaching were completed. Fourteen students were graduate entry while the remainder were undergraduates. Several learning objectives were identified including understanding and management of Eating Disorders, understanding the differences between presentations in adults and children, and management of suicidal ideation and self-harm. Clinical questions and accurate response rate are outlined in table 1 . In terms of qualitative feedback, most students found their learning objectives had been met. Case based discussion and interaction were valued. However, others reported overlaps with the adult psychiatry curriculum and disliked aspects of the format. Conclusion: Despite subject topics being available in advance, there was an evident lack of knowledge in some areas. Interactive case base approaches were preferred by students. Qualitative feedback highlighted aspects of the teaching which students found unhelpful and has led to modification of the lectures for further groups and a change in structure of the session for future medical students in the medical school.